(untitled) (Web of Teachers: Inderscience Research, 2026)
Biodiversity is conventionally measured by the variety of plants, animals, and fungi visible to the naked eye. Yet this macroscopic perspective captures only a fraction of the living world. The true breadth of biological diversity resides in the microscopic realm of bacteria, archaea, fungi, protists, and viruses—organisms that have governed Earth’s chemistry for billions of years and continue to underpin the existence of all larger life forms. Despite their invisibility, microorganisms are far more than a passive background; they are the principal architects of the biosphere. This thesis argues that microorganisms serve as the fundamental drivers of biodiversity through four interrelated roles: they operate the global biogeochemical cycles that sustain life, they form obligate symbiotic relationships that enable the evolution and diversification of multicellular organisms, they act as powerful evolutionary catalysts that continuously generate genetic novelty, and they confer resilience to ecosystems facing environmental perturbation. A comprehensive understanding of biodiversity therefore demands that microorganisms be placed at its very center.